Impacts of financial distress on real and accrual earnings management - Muljono, Danella Rachel; Suk, Kim Sung (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
This research investigates the impact of financial distress on the magnitude of different earnings management approaches, namely real earnings management and accruals earnings management. This research utilizes a total of 2002 firm-year observations from 259 publicly-listed companies and 20 sub-industries in Indonesia from the year 2005 to 2014. Financial distress causes a significant increase of real earnings management and a significant decrease of accruals earnings management. It means that the healthier the company, the bigger the magnitude of real earnings management that is conducted through managing production costs and discretionary expenses. On the other hand, the lower the financial health of the company, the bigger the magnitude of accruals earnings management that is conducted through managing discretionary component of accruals.